Peran Otoritas Jasa Keuangan dalam Pengawasan dan Penindakan Pelanggaran Hukum Perbankan di Indonesia - Abyasa Abrar Nugroho; Aryasatya Yusuf Wiryawan; Maglyn Angel Stefanny; Nurfadilla Risa Aulia; Ayu Maharsuci Nindya Mahyudi; Baidhowi Baidhowi (Jurnal Intelek Dan Cendikiawan Nusantara, 2026)
The banking sector plays a vital role in maintaining national economic stability, necessitating a robust and integrated supervisory framework. This study examines the supervisory authority and enforcement mechanisms of the Financial Services Authority (Otoritas Jasa Keuangan/OJK) in addressing violations of banking law in Indonesia using a normative juridical method with statutory and conceptual approaches based on primary and secondary legal materials. The findings reveal that OJK holds comprehensive supervisory powers through compliance-based and risk-based supervision, implemented via on-site and off-site mechanisms, and supported by coordination with Bank Indonesia and the Indonesia Deposit Insurance Corporation (LPS). In enforcing regulations, OJK may impose graduated administrative sanctions, ranging from written warnings and fines to restrictions on business activities and revocation of banking licenses, while criminal violations are handled in coordination with law enforcement agencies. Despite an adequate regulatory framework, supervisory implementation faces challenges such as increasingly complex financial products, rapid technological innovation, and global economic dynamics, making strengthened inter-agency coordination and enhanced supervisory capacity essential to ensure compliance and sustain public confidence in the national banking system.